An overview of an enhanced multi-systems robotized digitizing. Issue 4 (4th July 2018) - Bordron, Matthias; Mehdi-Souzani, Charyar; Bruneau, Olivier
ABSTRACT: Robots were commonly used for repetitive tasks, but to date they can handle more demanding processes like digitizing. Using a robot gives many advantages even though they still have a lack of accuracy when following a path. This paper focuses on an optimization strategy to get the best quality or/and speed for 3D digitization supported by a robot. In this way, a path planning algorithm is introduced based on the exploitation of robot and digitizing sensor performances. In order to define the robot calibration and its performances assessment, an original adapted model is investigated. An optimization step is integrated to the path planning algorithm in order to identify the best path (regarding the digitizing quality and time) among a set of admissible one. Finally the implementation of the selected path planning is carried out and the robot is monitored by an external measurement system in charge to correct this path to ensure the quality of digitizing. GRAPHICAL ABSTRACT: